DIVERSITY AND STRATEGIC HUMAN RESOURCE MANAGEMENT: LITERATURE REVIEW - Sanghvi, Paarmita (PEOPLE: International Journal of Social Sciences, 2019)
This age of globalisation has made the world seem smaller. Which has made companies claim their foothold in other cultural diversities. Making the workforce more diverse than ever, and it is still becoming diverse day by day. The interest in the term diversity began in the United States of America in the 1980s.Workforce diversity has been and is one of the main problem for a manager of human resource management in modern companies. And despite noticing this grave problem, various models in this field of human resource management consider workforce as homogenous and generic. Leaders need to understand the need for managing diverse organization to their own strengths than neglecting or looking at it from just one viewpoint. This will increase efficiency and productivity of the organization as diverse teams will produce better results and the organization will gain a market advantage. The main aim of this paper is to view the literature of diversity among employees in strategic human resource management. Nevertheless, the efforts to develop and understand cross-culturality and diversity-oriented models still remain underdeveloped. The objective being, identifying limitations in previous research to drive positive future research in this field with newer models to determine a solution to this problem. There is a need to create strategies that create cultural environments incorporating values of humanity. And what this paper suggests is that we need is a completely new set of strategies of the human resource management to manage a heterogeneous workforce.